ИНТЕГРАЦИЯ ЭЛЕМЕНТОВ ВЫСШЕЙ МАТЕМАТИКИ В СРЕДНЮЮ ОБЩЕОБРАЗОВАТЕЛЬНУЮ ШКОЛУ: МЕТОДЫ И ПОДХОДЫ К ОБУЧЕНИЮ - Алланазаров, Р.М. (SCIENCE and SOCIETY, 2023)
This thesis investigates the integration of higher mathematics elements into the teaching methods of secondary general education schools. It discusses the advantages of this approach, such as developing critical thinking and analytical skills in students and preparing them for solving complex problems in their future careers. Various teaching methods, including game-based learning, project-based learning, and technology integration, are presented as effective means to implement this approach.
Keywords: higher Mathematics; Teaching Methods; Secondary Education; Game-Based Learning; Project-Based Learning; Technology Integration; Differentiated Instruction; Teacher Training